2019
DOI: 10.1016/j.aott.2019.04.002
|View full text |Cite
|
Sign up to set email alerts
|

One step treatment of talus osteochondral lesions with microfracture and cell free hyaluronic acid based scaffold combination

Abstract: ObjectiveThe aim of this study was to assess the effectiveness of microfracture and cell free hyaluronic acid (HA) based scaffold combination in the treatment of talus osteochondral defects (OCD).MethodsThis study retrospectively evaluated the clinical results of the 20 patients (14 males and 6 females, mean age at the time of surgery: 32.9 years (range: 16–52 years)) who were treated with MFx and cell-free HA-based scaffold combination for talus OCD smaller than 1.5 cm2 and deeper than 7 mm. Results were eval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 34 publications
(41 reference statements)
0
16
0
Order By: Relevance
“…These features commit AMIC of special interest of both patients and surgeons. Several studies showed promising results of AMIC for talar chondral defects, with high patient satisfaction and quick return to sport [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24]. We identified only three long term studies investigating efficacy and feasibility of AMIC [12,15,21].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These features commit AMIC of special interest of both patients and surgeons. Several studies showed promising results of AMIC for talar chondral defects, with high patient satisfaction and quick return to sport [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24]. We identified only three long term studies investigating efficacy and feasibility of AMIC [12,15,21].…”
Section: Discussionmentioning
confidence: 99%
“…A cell-free resorbable membrane is then trimmed and ensured over the defect, to create a blood clot rich in stem cells [9]. Several studies which focused on AMIC for chondral defects of the talus demonstrated high rate of patient satisfaction [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24]. However, evidence concerning the midterm efficacy and safety of AMIC are limited.…”
Section: Introductionmentioning
confidence: 99%
“…In our study, we observed a histologically significant difference at Week 4 in the control group, while the histological and macroscopic scoring was significantly higher in the experimental group at Week 8. Yontar et al [35] applied MF-HA-based scaffold combination in the treatment of talus osteochondral defect and concluded that it was a safe and effective technique with good clinical results for lesions deeper than 7 mm. In our study, adipose-derived SVF increased the efficacy of MF-HA-based scaffold combination used in osteochondral treatment, particularly in the late period, and we were able to show this effect macroscopically and histologically.…”
Section: Discussionmentioning
confidence: 99%
“…Besides weak evidence of ankle osteoarthritis, there are studies that show good results with HA injection for primary OLT has proven to have the quite favorable results. 8,30…”
Section: Discussionmentioning
confidence: 99%
“…Besides weak evidence of ankle osteoarthritis, there are studies that show good results with HA injection for primary OLT has proven to have the quite favorable results. 8,30 To our knowledge, no previous study has investigated HA treatments for recurrent or unresolved ankle pain after arthroscopic bone marrow stimulation. Only a few studies on the use of HA in OLT have been published.…”
Section: Discussionmentioning
confidence: 99%